Trait Preference and Performance Evaluation of Indigenous Goat Keepers of Borana Pastoralists in Ethiopia - Mohammed, Hussein; Tesema, Birhanu (Annals of Arid Zone, 2024)
The objectives of this study were to assess the growth and reproductive performance of goats in a pastoral and agropastoral area and Borana-Pastoralists’ preferences for the traits of the indigenous goats. A total of 97 households were interviewed and a total of 194 goats were tracked for six months to collect data. The collected data were analysed using SAS’s GLM and descriptive statistics. The results indicated that pastoralists in the study areas were practicing extensive production systems. The ratio of males to females aged less than six months was proportional. However, females over six months of age outnumbered males proportionally. The overall mean body weight (kg) in the pastoral study area at 0, 90, and 180 days of age were 2.37, 10.5, and 13.8, respectively. Similarly, in agro-pastoral study areas, the result was 2.41, 10.6, and 14.01 kg. The effect of birth type affected the growth of goats with a similar trend and consistently up to weaning was significant (P